Youth, Arts, and Education : Reassembling Subjectivity through Affect. - Hickey-Moody, Anna (Routledge advances in sociology., 2013)
How are the arts important in young people's lives? Youth, Arts and Education offers a groundbreaking theory of arts education. Anna Hickey-Moody explores how the arts are ways of belonging, resisting, being governed and being heard. Through examples from the United Kingdom and Australia, Anna Hickey-Moody shows the cultural significance of the kinds of learning that occur in and through arts. Drawing on the thought of Gilles Deleuze, she develops the theory of affective pedagogy, which explains the process of learning that happens through aesthetics. Bridging di.